COVID-19 and the Egyptian economy: From reopening to recovery: Alternative pathways and impacts on sectors, jobs, and households - Breisinger, Clemens; Raouf, Mariam; Wiebelt, Manfred; Kamaly, Ahmed; Karara, Mouchera (International Food Policy Research Institute, 2020)
Although the global economy is forecasted to shrink by 4.4 percent in 2020 (IMF 2020), the Egyptian economy is proving resilient to the immense human and financial costs caused by the global COVID-19 pandemic. This resilience is mainly explained by the successful implementation of the economic reform program since 2016 that provided more fiscal space to withstand the adverse impact of the COVID-19 crisis. However, that Egypt’s economy is holding up is also due to the rapid response and proactive measures to limit the impact of the virus that were implemented by the Egyptian Government since March 2020 (MPED 2020). These enabled the country to avoid a full lockdown policy (Figure 1). While Egypt posted negative economic growth rates from April to June 2020 at the height of the crisis, overall economic growth was still positive at 3.6 percent for fiscal year (FY) 2019/20. This estimate is only slightly lower than the initial projection of the impact of the pandemic on Egypt’s economy of an annual economic growth equal to 3.8 percent, as estimated by staff of the International Food Policy Research Institute (IFPRI) and the Ministry of Planning and Economic Development (MPED) (Breisinger et al. 2020). The deviation between the early and final estimate can be mainly explained by the lower than expected growth rates in the manufacturing and health services sectors and the better than expected performance of the trade and transport sectors. A joint note by the International Food Policy Research Institute and the Ministry of Planning and Economic Development of the Government of the Arab Republic of Egypt.